Optimization of Operational Parameters for Removal of Reactive Red 195 from Synthetic Wastewater by Sequential Redox Process - Noreen, A.; Nosheen, S.; Nisar, M.; Majeed, I.; Saleem, A.; Yousaf, M.I. (Asian Journal of Chemistry, 2012)
The effectiveness of a combined reduction-oxidation treatment system for the removal of reactive red 195 (RR 195) from the synthetic wastewater was investigated. In this treatment system, sodium sulphite (Na2SO3) was used as reducing agent and potassium permanganate (KMnO4), hydrogen peroxide (H2O2) and ferrioxalate [Fe(OX)] were employed as oxidizing agents. The influence of pH, concentration of reducing agent and oxidizing agents and initial concentration of dye was examined in the lab scale experimental studies. Spectroscopical results indicated that H2O2 and ferrioxalate in combination with Na2SO3 decolourized 63.61 and 71.28 % of reactive red 195, respectively, at optimized conditions while KMnO4 alone showed 99.34 % decolourization efficiency. The water quality was also monitored by chemical oxygen demand and total organic carbon. There was reduction in chemical oxygen demand and total organic carbon values, which indicated chemical decomposition of recalcitrant complex structure of dye. FT-IR analysis of products obtained after sequential treatment also confirmed the degradation during the process. Overall comparison revealed that potassium permanganate had excellent potential to decolourize reactive red 195.